Modifiable factors associated with cognitive resistance in the Framingham Heart Study. (31st December 2021) - Hwang, Phillip H; Mez, Jesse; Farrer, Lindsay A; Devine, Sherral; Auerbach, Sandford H; Qiu, Wendy; Liu, Chunyu; Au, Rhoda
Abstract: Background: Cognitive resistance to Alzheimer's disease (AD) refers to an individual's capacity to avoid the appearance of Alzheimer's dementia syndrome in the context of risk factors on pathologic processes. We sought to identify associations between potential modifiable risk factors for AD and cognitive resistance. Method: 2, 318 participants from the Offspring and Omni cohorts in Framingham Heart Study without prevalent dementia and at high risk for AD were selected. High risk for AD was defined as having ≥2 of the following risk factors measured at baseline: (1) age >80 years; (2) diagnosis of cardiovascular disease or coronary heart failure; (3) carrier of ≥1 APOE ε4 allele; (4) plasma Aβ42/40 ≤0.1049 (Perez‐Grijalba et al.; 2019); (5) C‐reactive protein level ≥10 mg/L (Morley and Kushner; 1982); and (6) female sex. Cognitively resistant individuals were defined as those at high risk for AD that did not progress to a clinical diagnosis of dementia/AD. Standardized research criteria were used to ascertain all‐cause dementia and AD. Potential modifiable risk factors for AD measured at baseline included diabetes, hypertension, obesity, depression, smoking, and education. Logistic regression was used to examine associations between these factors and cognitive resistance to AD. Result: Over an average period of 36 years, absence of diabetes (OR = 3.63; 95% CI = 2.37 – 5.55; p <0.001) and absence of hypertension (OR = 1.60; 95% CI = 1.02 – 2.51; p = 0.038), as well as not smoking (OR = 2.10; 95% CI = 1.41 – 3.13; p <0.001), at baseline were significantly associated with cognitive resistance. Absence of depression, absence of obesity, or high education were not associated with cognitive resistance. Conclusion: Individuals at high risk for AD who do not have diabetes or hypertension, or do not smoke may be cognitively resistant to AD. These findings support the heart‐brain connection for dementia prevention and healthy cognitive aging.